Urgensi Penggunaan Kertas Berbahan Dasar Limbah Cangkang Kelapa Sawit Bagi Peserta Didik di SMK Pertanian Pada Proses Pembelajaran - Rindu Ayu Mulia Dewi; Wulan Garnasih; Gani Firmansyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The conventional type of paper that is still widely used by students to support the learning process in schools is printed modules. Even though digitalization such as ebooks is starting to be used by the public, printed modules are still used to simplify the teaching process in the classroom. The types of paper that are generally used do not all use environmentally friendly paper such as paper from palm oil shell waste processing, due to a lack of in-depth knowledge. This research is a qualitative research that uses interview methods with several students from three different skills programs at one of the Bandung City Agricultural Vocational Schools to measure knowledge about environmentally friendly paper. Participants were asked six questions related to the use of paper in schools, understanding of environmentally friendly paper, and knowledge about paper produced from processing palm oil shell waste. The results show that the majority of students do not know clearly about processing waste from palm oil shells into environmentally friendly paper, but the data shows that alternative types of environmentally friendly paper are needed to participate in preserving environmental welfare and improving economic aspects.